Digital Natives - Piscitelli, Alejandro (2008)
Digital migration is an ongoing process. This article studies what is happening between the yesterday digital migrants and today digital natives. Digital migration cannot be reduced to just technological convergence affairs, but it should also explore the generational gap between the natives and the migrants, and the issues regarding epistemological discontinuity, which we all have to deal with. Without this knowledge, it is impossible to understand what is happening with today’s digital native generation education and culture.